DESAIN PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM TRANSDISIPLIN - Edi Nurhidin; Maimunatun Habibah (JP : JURNAL PENDIDIKAN, 2021)
Abstract: This article discusses the transdisciplinary Islamic education curriculum. Where the transdisciplinary approach takes a position as the final set of integrated curriculum concepts. This positioning indicates that this approach is difficult to use. However, the rapid advancement of science and technology actually places it as an alternative approach in reforming the curriculum structure that accommodates all potential students so that they have meaningful knowledge, namely knowledge that is generalist and has a relationship with solving real life problems. The application of the trans-disciplinary approach is a strategic step to realize the concept of integrated scientific integration that involves collaboration and dialogue between disciplines and actors outside the discipline (cross-sector of society) which leads to the birth of new forms of interdisciplinary relationships to achieve problem solving, innovation, creativity and transformation based on real experiences. Curriculum development and transdisciplinary learning are also becoming increasingly relevant because it opens up opportunities for the creation of new discoveries or sciences as a result of a combination of various disciplines involving religion, natural sciences, and social sciences and humanities because the transdisciplinary curriculum is the most integrated curriculum model.Keywords: Consciousness, Curriculum Design, Islamic Education